2018
DOI: 10.5607/en.2018.27.5.419
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment with Combined Chemotherapeutic Agents Affects Hippocampal Micromorphometry and Function in Mice, Independently of Neuroinflammation

Abstract: Chemotherapeutic agents induce long-term side effects, including cognitive impairment and mood disorders, particularly in breast cancer survivors who have undergone chemotherapy. However, the precise mechanisms underpinning chemotherapy-induced hippocampal dysfunction remain unknown. In this study, we investigated the detrimental effects of chronic treatment with a combination of adriamycin and cyclophosphamide (AC) on the neuronal architecture and functions of the hippocampi of female C57BL/6 mice. After chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 67 publications
0
29
1
1
Order By: Relevance
“…Changes in the shape or size of the dendritic spines affect their stability and synaptic transmission [29]. Kang et al found that AC treatment significantly decreased number of mushroom spines in the CA1 neurons of female black mice [28]. We did not see a change in the proportion of mushroom spines after AC-T treatment in the DG or CA1 neurons.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…Changes in the shape or size of the dendritic spines affect their stability and synaptic transmission [29]. Kang et al found that AC treatment significantly decreased number of mushroom spines in the CA1 neurons of female black mice [28]. We did not see a change in the proportion of mushroom spines after AC-T treatment in the DG or CA1 neurons.…”
Section: Discussioncontrasting
confidence: 52%
“…Interestingly, chemotherapy drugs have been found to negatively impact dendritic branching. Chronic AC treatment significantly reduces total dendritic length and complexity in the hippocampus of female C57BL/6 mice [28]. We found that AC-T chemotherapy decreased dendritic length and complexity in the DG and CA1 regions of the hippocampus.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations